O hábito da leitura na sala de aula na concepção de Paulo Freire - Carvalho, Karoline Martins de (Universidade Federal do Tocantins, 2023)
Reading is capable of resignifying meanings, therefore, questions what elements are needed to disseminate the habit of reading in the classroom. Based on this question, this article aims to analyze the importance of the dissemination of reading habits in the classroom based on freiriatheoretical theoretical assumptions. The conception Freiriana on the act of reading brings reflections of cognitive dimensions with proposals of (re) organization of the methodology in teaching. It is important to study about reading, since the act of reading contributes to the construction of more reflective/critical. This is research a bibliographic based on studies in books, journals, articles and specialized websites, authors such as Freire (1989, 1993, 2009), Gadotti (1996), Geraldi (2010), Martins (1982) and Menezes (2014). Some results indicate that disseminating the act of reading in the classroom is to understand that the training of readers depends on how it is being built and in addition to knowing how to read, it is essential to like the content in which you are reading, these stimuli are the basis for the student's critical training.